A comparative assessment of growth performance, haematology and serum biochemistry of hybrid catfish fed non-conventional plant proteins in homestead concrete tanks (2000)
An 84-day experiment was carried out to evaluate the potentials of three non-conventional plant proteins groundnut cake (GNC), soyebean cake (SBC) and sesame seed cake (SSC) singly and combined in the diets of hybrid catfish grown in homestead concrete tanks. Triplicate groups of 30 juveniles average weight of 26.9+ 0.18g were fed four diets which were formulated to contain 30% crude protein with 25% of the GNC (diet 1) component replaced by SBC (diet 2), SSC (diet 3) and a combination of the three in diet 4. All the diets contained an equal amount of animal protein (25.43g). At the end of 84 days of feeding, growth parameters, feed and carcass proximate analyses, mortality, haematology and serum biochemical parameters were measured. The results showed that the diets affected the growth of the juveniles significantly (P<0.05). The percentage weight gain of the fish fed diet 1 was 204% of the initial weight, while those fed diets 2, 3 and 4 were 405%, 465% and 445% respectively. Protein Efficiency Ratio (PER) was significantly higher (P <0.05) in diets 2, 3 and 4 than in diet 1, with diet 4 having the highest PER. The percent specific growth rate (SGR) recorded for each diet was not significantly different (P>0.05) from each other. Percentage mortality were 22.2%, 13.3%, 5.6% and 3.3% in fish fed diets 3, 4, 2 and 1, respectively. There were no significant variations in haematological parameters of fish fed all the various diets, except for those on diet 3 which exhibited lymphopenia and heterophilia (P<0.05). Similarly, there were no significant variations in serum biochemical parameters, except for hyperfibrinogenaemia, hypoglyeaemia and significantly increased AST activities (P<0.05) in fish fed diet 3 and 4. There were significant increases in the serum levels of cholesterol and triglyceride in fish fed diets 2 (P<0.05), 3 and 4 (P<0.01). The findings in this study showed that even though SBC and SSC inclusions in fish diet resulted in better growth performance than GNC inclusion, the relatively high levels of crude fat in these plants proteins especially SSC, may in fact be injurious to fish by causing fat deposition in tissues, fatty hepatic and renal damage, artherosclerosis and coronary heart disease both of which will predispose the fish to stress, innocuous disease and mortality.